Improving the working motivation of officers in Cai Nuoc district, Ca Mau province - Nguyễn, Bé Sáu (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The research investigated the fact of improving the working motivation of the officers in Cai Nuoc district, Ca Mau province to evaluate the impacts on working motivation of the officers in Cai Nuoc district and emphasize the management implications on enhancing the working motivation of the officers in Cai Nuoc district, Ca Mau province. The research used Cronbach’s Alpha analysis method, exploratory factor analysis and regression analysis, based on the research results, the management implications includes: (1) Social welfare policy; (2) Job characteristics; (3) Working conditions; (4) Opportunities for promotion; (5) Recognition; (6) Salary regime; (7) Relationship with colleagues; (8) Relationship with superiors.